Social housing programme of Selangor Zakat Board of Malaysia and housing satisfaction - Mohit, Mohammad Abdul; Nazyddah, Nurul (Springer New York LLC, 2011)
Social housing in Malaysia is provided through the public and private sectors.Recently, the Selangor Zakat Board (SZB) has started to provide social housing in the state of Selangor, Malaysia. Up to 2007, a total of 906 units have been delivered under its different programmes. This paper evaluates these programmes by adopting the housing satisfaction model which is currently used as a customer satisfaction tool for public/private housing in many local governments in the UK and USA. The main purpose of this paper is to identify the types of housing programmes adopted by SZB and examine beneficiaries’ housing satisfaction in each programme on a comparative plane. In order to examine housing satisfaction, five objective components of satisfaction—housing unit features,housing unit support services, the social environment, public facilities and neighbourhood facilities—were analysed through beneficiaries’ levels of satisfaction which were measured by applying a Likert scale. The findings of the paper indicate that SZB has been successful in providing a moderate level of satisfaction with the housing unit. However, the existence of variable levels of satisfaction with other components implies that there is still scope to enhance residents’ satisfaction with those components.